In the mind of the beholder: Narcissism relates to a distorted and enhanced self-image. (April 2021) - Steiner, Troy G.; Levy, Kenneth N.; Brandenburg, Joseph C.; Adams, Reginald B.
Abstract: To date, prominent theories still disagree on whether the pathological grandiosity that underlies narcissism stems from a defensive, compensatory process in response to insecurity or from years of unjustified overvaluation during formative stages of development. Across two studies, we introduce a novel method to test these theories by examining visual representations of self. In Study 1, we measured Self-Concept Clarity and the distortion of (n = 96) participants' self-images (generated using the reverse correlation technique) relative to their actual appearances. In Study 2, we then compared attractiveness ratings of the actual photographs of participants with their self-images generated in Study 1, through judgments made by independent raters (n = 45). Our work revealed that a) lower Self-Concept Clarity predicts self-image distortion, b) the narcissistic desire to conceal flaws mediates this association, and c) self-image distortion led to self-enhancement, consistent with a compensatory reaction to insecurity. Highlights: Our work is the first, to our knowledge, to examine self-image as a visual percept. Novel use of psychophysical task for studying and assessing narcissism aggrandizement Findings suggest aggrandizement stems from insecurity, (cf. grandiose fantasy). Self-image distortion relates to self-image enhancement via narcissistic insecurity.